Thermal interface composite polymer materials - Oleksandr Listratenko; Yuriy Shepetov; Oleksandr Kravchenko; Illia Borshchov; Bohdan Podlesnyi (Авіаційно-космічна техніка та технологія)
The subject of the article is the analysis and development of new thermally conductive composite polymer materials used for improved heat dissipation in electronics. The goal of the work is to create effective composites based on polyimides and silicone binders using aluminum nitride fillers. The use of microfillers made of white aluminum nitride powders with micron-sized particles in polymer matrices enables the development of new composite materials with enhanced thermal conductivity for use in the assembly and sealing of electronic devices. The methods employed include numerical modeling of thermal conductivity using the COMSOL Multiphysics software suite and experimental studies of thermal conductivity by the steady-state heat flow method. The results show that in the theoretical models of the developed thermally conductive composite materials, aluminum nitride powders with a particle size of 10 µm and thermal conductivity of about 50–60 W/(m·K) were used as microfillers in polymer matrices. This was experimentally confirmed by studying the aggregation processes of these powders in polymer dispersions during the fabrication of thermally conductive composite polyimide and silicone materials. At an average filler concentration of 45 vol.% AlN particles, the thermal conductivity of experimental samples of thermal interface materials reached 1.09 W/(m·K), which corresponds well with theoretical predictions. The conclusions state that such materials can significantly improve heat dissipation efficiency in electronic devices and may find applications in the aerospace, energy, and other industrial sectors.